Eco-creativity generative architecture an upcycled art village and ecopark towards a culture of circularity - Alabanza, Terena Joelle S.
Waste pollution in the Philippines is the result of increasing waste production and its mismanagement, especially in terms of materials that are not accepted by recycling facilities. The absence of a circular system to address this has resulted in large volumes of unrecyclable waste materials ending up in landfills, streets, and waterways. Studies have highlighted how circularity can be achieved using waste infrastructure that processes recyclable materials into raw materials for new products; however, discarded materials that conventional recycling facilities cannot process remains unaddressed. To extend the closed-loop system of recycling beyond conventional recyclable materials, such as plastic bottles and paper, it is necessary to reimagine the recycling system as one that also repurposes and upcycles materials, rather than merely processing recyclable materials. However, efforts to resolve the issue of discarded waste will only be effective if the general public’s lack of eco-consciousness is addressed through community involvement and the democratization of waste repurposing activities. Thus, this study explores how architecture can generate ecocreativity to foster a culture of circularity by increasing awareness of environmental issues and introducing creative means of repurposing material waste. This is achieved through an upcycled art village and ecopark in Imus, Cavite, which primarily repurposes reusable material waste into artworks and community innovations.